Genetics of strabismus - Martinez Sanchez, Mayra; Whitman, Mary C. (Frontiers in Ophthalmology, 2023)
Strabismus, or misalignment of the eyes, is the most common ocular disorder in the pediatric population, affecting approximately 2-4% of children. Strabismus leads to disruption of binocular vision, amblyopia, social and occupational discrimination, and decreased quality of life. While it has been recognized since ancient times that strabismus runs in families, the inheritance patterns are complex, and the precise genetic mechanisms have not been defined. Family, population, and twin studies all support a role of genetics in development of strabismus. Complicating all studies of strabismus, there are multiple forms of strabismus, and it is not known if they have shared genetic mechanisms or are distinct genetic disorders. Studies assuming strabismus is a Mendelian disorder have found areas of linkage and candidate genes in particular families, but no definitive casual genes. Genome-wide association studies searching for common variation that contributes to strabismus risk have identified two risk loci and three copy number variants in Caucasian populations. Causative genes have been identified in congenital cranial dysinnervation disorders, syndromes in which eye movement is limited or paralyzed. The causative genes lead to either improper differentiation of cranial motor neurons or abnormal axon guidance. This article reviews the evidence for a genetic contribution to strabismus and the recent advances that have been made in the genetics of comitant strabismus, the most common form of strabismus.